Screening Risiko Terjadinya Deep Vein Trhombosis - Elfi Etikasari; Nur Chayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to examine several studies on early screening and prevention of the risk of developing Deep Vein Thrombosis (DVT). The method used in this literature review consists of 4 stages: (1) identification of the search for journal articles; (2) identification of literary works based on title, abstract, and purpose; (3) inclusion criteria; (4) complete and specific texts are available according to the purpose of the review. The process of searching for journal articles using Google Scholar, ScienceDirect, DOAJ, Scopus, ProQuest, Ebsco and Pubmed. The results showed that most early DVT screenings used ultrasound as a non-pharmacological DVT detection and prevention tool, the most frequently used was compression stockings. In conclusion, compression stockings are more effective in preventing DVT. Keywords: Early Detection, DVT, Bed Rest